Correlation of PD‐L1 expression with CD8+ T cells and oxidative stress‐related molecules NRF2 and NQO1 in esophageal squamous cell carcinoma - Xin Zhang; Yanan Yang; Hongying Zhao; Zhongqiu Tian; Qing Cao; Yunlong Li; Yajuan Gu; Qinfei Song; Xiumei Hu; Mulan Jin; Xingran Jiang (Wiley, 2024)
Abstract Oxidative stress and the immune microenvironment both contribute to the pathogenesis of esophageal squamous cell carcinoma (ESCC). However, their interrelationships remain poorly understood. We aimed to examine the status of key molecules involved in oxidative stress and the immune microenvironment, as well as their relationships with each other and with clinicopathological features and prognosis in ESCC. The expression of programmed death‐ligand 1 (PD‐L1), CD8, nuclear factor erythroid‐2 related factor‐2 (NRF2), and NAD(P)H quinone oxidoreductase 1 (NQO1) was detected using immunohistochemistry in tissue samples from 176 patients with ESCC. We employed both combined positive score (CPS) and tumor proportion score (TPS) to evaluate PD‐L1 expression and found a positive correlation between CPS and TPS. Notably, PD‐L1 expression, as assessed by either CPS or TPS, was positively correlated with both NRF2 nuclear score and NQO1 score in stage II-IV ESCC. We also observed a positive correlation between the density of CD8+ T cells and PD‐L1 expression. Furthermore, high levels of PD‐L1 CPS, but not TPS, were associated with advanced TNM stage and lymph node metastases. Moreover, both PD‐L1 CPS and the nuclear expression of NRF2 were found to be predictive of shorter overall survival in stage II-IV ESCC. By using the Mandard‐tumor regression grading (TRG) system to evaluate the pathological response of tumors to neoadjuvant chemotherapy (NACT), we found that the TRG‐5 group had higher NRF2 nuclear score, PD‐L1 CPS, and TPS in pre‐NACT biopsy samples compared with the TRG‐3 + 4 group. The NQO1 scores of post‐NACT surgical specimens were significantly higher in the TRG‐5 group than in the TRG 3 + 4 group. In conclusion, the expression of PD‐L1 is associated with aberrant NRF2 signaling pathway, advanced TNM stage, lymph node metastases, and unfavorable prognosis. The dysregulation of PD‐L1 and aberrant activation of the NRF2 signaling pathway are implicated in resistance to NACT. Our findings shed light on the complex interrelationships between oxidative stress and the immune microenvironment in ESCC, which may have implications for personalized therapies and improved patient outcomes.